Description of Professional Fee for Pharmacist in Sleman - Hardika Aditama; A. Saputri; D. Fadhilah; K. Mayningrum; A. Sawitri; W.A. Pratiwi; I.N. Pristhifani (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Pharmacist is a profession whose existence is needed by community. However, within the community of pharmacy itself, the presence of pharmacist is quite alarming. One of the causes of low pharmacist who desire to practice in the community of pharmacy is the low level of professional fee offered. This study aimed to describe professional fee received by pharmacist and the workload of pharmacist in Sleman. This study was a descriptive non-experimental that was conducted in Sleman in August 2017. Population of this study was a pharmacist who practiced in community of pharmacy in Sleman. Total of 170 respondents from 128 pharmacies were involved in this research. However, 6 questionnaires cannot be analyzed because it is not completely filled. The highest amount of professional fee is between Rp 2.000.000-Rp 3.000.000. Almost all respondents (78%) stated the amount of professional fee that was received was not as expected. The workload of pharmacists is not so heavy and most of the patient are self medication. Pharmacists at the community of pharmacy should be able to show a better work performace, which is shown by increasing pharmacy revenues to get a better rewards.